Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Derive three equation of motion

Asked by 22nd October 2013, 1:29 PM
Answered by Expert
Answer:

(1) First equation of Motion: v = u + a t

Consider a body of mass m having initial velocity u.

Let after time t its final velocity becomes v due to uniform acceleration a.

Now we know that:
Acceleration = Change in velocity / Time taken

Acceleration = (Final velocity - Initial velocity) / Time taken

  a = v - u / t
 a t = v - u

or  v = u + a t

This is the first equation of motion.


(2) Second equation of motion: s = u t + 1/2 at2

Let the distance travelled by the body be s.

We know that
Distance = Average velocity x Time

Also, Average velocity = (u + v) / 2

.:  Distance (t) = (u + v) / 2 t            .eq.(1)

Again we know that:

v = u + at

Substituting this value of v in eq.(1), we get

s = (u + u + a t) / 2 t
s = (2 u + a t) / 2 t
s = (2 u t + a t2) / 2
s = (2 u t / 2) + (a t2 / 2)

or  s = u t + (1/2) a t2

This is the 2nd equation of motion.

 

(3) Third equation of Motion:  v2 = u2 +2 a s

We know that

v = u + a t
v - u = a t

or  t = (v - u) / a                                    ..eq.(2)

Also we know that


Distance = average velocity x Time

.: s = [(v + u) / 2] x [(v - u) / a]

s = (v2 u2) / 2 a

2 a s = v2 u2

or  v2 = u2 + 2 a s

This is the third equation of motion.

 

Answered by Expert 23rd October 2013, 4:57 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Free related questions

12th April 2017, 11:33 AM
10th April 2017, 12:31 PM
10th April 2017, 2:44 PM
25th April 2017, 6:25 PM
25th April 2017, 12:00 PM

Chat with us on WhatsApp